2016
DOI: 10.1021/acs.est.5b05503
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Conventional and Unconventional Natural Gas Production Sites in the Marcellus Shale Basin

Abstract: There is a need for continued assessment of methane (CH4) emissions associated with natural gas (NG) production, especially as recent advancements in horizontal drilling combined with staged hydraulic fracturing technologies have dramatically increased NG production (we refer to these wells as "unconventional" NG wells). In this study, we measured facility-level CH4 emissions rates from the NG production sector in the Marcellus region, and compared CH4 emissions between unconventional NG (UNG) well pad sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
197
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(213 citation statements)
references
References 20 publications
(71 reference statements)
14
197
2
Order By: Relevance
“…As shown in Fig. 8, compressor stations emitted most frequently (70 % emission frequency), which we expected based on the results of Omara et al (2016). However, due to our low sample size relative to well pads, we would need to sample more compressor stations to arrive at a statistically significant estimate.…”
Section: Emission Sources and Trendsmentioning
confidence: 70%
See 1 more Smart Citation
“…As shown in Fig. 8, compressor stations emitted most frequently (70 % emission frequency), which we expected based on the results of Omara et al (2016). However, due to our low sample size relative to well pads, we would need to sample more compressor stations to arrive at a statistically significant estimate.…”
Section: Emission Sources and Trendsmentioning
confidence: 70%
“…Our minimum detection limit of 0.59 g s −1 was used as the emission factor for wells. Facility emission volumes are from Omara et al (2016) amounts of infrastructure allows for a comparison between our CH 4 volume estimate and those of Peischl et al (2016) and Karion et al (2013).…”
Section: Methane Emission Inventory Estimatementioning
confidence: 99%
“…To convert the production rate into an emission rate, we need to assume a first guess as to the expected leakage from wells in the area. A first-guess natural gas emission rate of 0.13 % was applied to the production value of each of the 7000+ producing unconventional wells based on the median rate from Omara et al (2016). The natural gas emission rate was then converted to a CH 4 emission rate by assuming a CH 4 composition in the natural gas of 95 % (Peischl et al, 2015).…”
Section: Regional Methane Emission Inventorymentioning
confidence: 99%
“…Emissions from sources in the natural gas industry can be temporally variable and have a wide range of values depending on a number of factors, such as the quality and age of the device and the gas pressure moving through the component. Furthermore, recent studies have shown that a majority of emissions come from a small percentage of devices, often referred to as "super-emitters", creating a long-tail distribution of emission sources (Brandt et al, 2014;Omara et al, 2016;Zavala-Araiza et al, 2015Frankenberg et al, 2016). These factors make it difficult to sample enough devices and adequately describe the mean emission rate, thus allowing for significant representation errors in the emission factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation